2015
DOI: 10.1051/0004-6361/201526571
|View full text |Cite
|
Sign up to set email alerts
|

AGN feedback in action: a new powerful wind in 1SXPS J050819.8+172149?

Abstract: Context. Galaxy merging is widely accepted to be a driving factor in galaxy formation and evolution, while the feedback from actively accreting nuclei is thought to regulate the black hole-bulge coevolution and the star formation process. Aims. In this context, we focused on 1SXPS J050819.8+172149, a local (z = 0.0175) Seyfert 1.9 galaxy (L bol ∼ 4 × 10 43 erg s −1 ). The source belongs to an infrared-luminous interacting pair of galaxies, characterized by a luminosity for the whole system (due to the combinat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…At the end of this obscured phase, massive quasar-driven outflows blow away most of the cold gas reservoir, creating a population of "red-and-dead" gas-poor elliptical galaxies (e.g., Cattaneo et al 2009). Support for this picture -at least for the most luminous AGN -comes from observations of kpc-scale outflows of molecular gas (e.g., Feruglio et al 2010;Sturm et al 2011;Veilleux et al 2013;Cicone et al 2014), as well as of neutral and ionized gas (e.g., Nesvadba et al 2008;Alexander et aloutflows (UFOs, with velocities typically up to 0.1-0.4c) have been clearly detected in X-rays in a sizable sample of AGN at low redshift (e.g., Reeves et al 2003;Pounds et al 2003;Tombesi et al 2010Tombesi et al , 2012aTombesi et al , 2014Tombesi et al , 2015Giustini et al 2011;Patrick et al 2012;Gofford et al 2013Gofford et al , 2015King et al 2014;Nardini et al 2015;Ballo et al 2015; see also Cappi 2006 for an early review; and Fabian 2012 for a more recent one) and also in a limited number of high-redshift quasars (e.g., Chartas et al 2002Chartas et al , 2007Chartas et al , 2009Chartas et al , 2014Saez et al 2009;Lanzuisi et al 2012). Although original claims of blueshifted absorption features were strongly debated (see Vaughan & Uttley 2008), recent high photon statistics in X-ray spectra of both radio-quiet (e.g., Tombesi et al 2010Tombesi et al , 2011Tombesi et al , 2012aGofford et al 2013) and radio-loud AGN (e.g., Gofford et al 2013;Tombesi et al 2014) have undoubtedly shown that these outflows are not ra...…”
Section: Introductionmentioning
confidence: 99%
“…At the end of this obscured phase, massive quasar-driven outflows blow away most of the cold gas reservoir, creating a population of "red-and-dead" gas-poor elliptical galaxies (e.g., Cattaneo et al 2009). Support for this picture -at least for the most luminous AGN -comes from observations of kpc-scale outflows of molecular gas (e.g., Feruglio et al 2010;Sturm et al 2011;Veilleux et al 2013;Cicone et al 2014), as well as of neutral and ionized gas (e.g., Nesvadba et al 2008;Alexander et aloutflows (UFOs, with velocities typically up to 0.1-0.4c) have been clearly detected in X-rays in a sizable sample of AGN at low redshift (e.g., Reeves et al 2003;Pounds et al 2003;Tombesi et al 2010Tombesi et al , 2012aTombesi et al , 2014Tombesi et al , 2015Giustini et al 2011;Patrick et al 2012;Gofford et al 2013Gofford et al , 2015King et al 2014;Nardini et al 2015;Ballo et al 2015; see also Cappi 2006 for an early review; and Fabian 2012 for a more recent one) and also in a limited number of high-redshift quasars (e.g., Chartas et al 2002Chartas et al , 2007Chartas et al , 2009Chartas et al , 2014Saez et al 2009;Lanzuisi et al 2012). Although original claims of blueshifted absorption features were strongly debated (see Vaughan & Uttley 2008), recent high photon statistics in X-ray spectra of both radio-quiet (e.g., Tombesi et al 2010Tombesi et al , 2011Tombesi et al , 2012aGofford et al 2013) and radio-loud AGN (e.g., Gofford et al 2013;Tombesi et al 2014) have undoubtedly shown that these outflows are not ra...…”
Section: Introductionmentioning
confidence: 99%
“…The system is at an early stage of merger (11.3 kpc distance) and is known to host an AGN that has optically been classified as Seyfert 2 plus a normal galaxy. The AGN, which is also the component in the system that displays water maser emission, hosts a molecular outflow and probably also a disc wind (Yamashita et al 2017;Ballo et al 2015). NGC 3783 is one of the most intensively monitored Seyfert galaxy at high energies.…”
Section: Appendix B: Maser Typesmentioning
confidence: 99%
“…2), characterized by a low outflow velocity (v out ∼ 100−1000 km s −1 ), are found in about 65% of the soft X-ray (E 2 keV) spectra of nearby AGN, and they are often known as warm absorbers (WAs, e.g., Halpern 1984;Blustin et al 2005;McKernan et al 2007;Laha et al 2014). More than 30% of the X-ray detected AGN show evidence of ultra-fast outflows (UFOs, e.g., Chartas et al 2002;Pounds et al 2003a,b;Braito et al 2007;Tombesi et al 2010Tombesi et al , 2015Gofford et al 2013;Nardini et al 2015;Ballo et al 2015). UFOs are extremely highly ionized (log(ξ/erg cm s −1 ) ∼ 3−6) absorbers that are detected as blueshifted absorption lines of Fe XXV and XXVI, with typical outflow velocity of v out ∼ 0.1c, but are capable of reaching near-relativistic values of ∼0.5c (e.g., Reeves et al 2018;Luminari et al 2021).…”
Section: Introductionmentioning
confidence: 99%